Structural characteristics of silica sonogels prepared with different proportions of TEOS and TMOS - Vollet, D. R. [UNESP]; Nunes, L. M. [UNESP]; Donatti, D. A. [UNESP]; Ruiz, Alberto Ibanez [UNESP]; Maceti, H. (Elsevier B.V., 2008)
Sonohydrolysis of mixtures of tetraethoxysilane (TEOS) and tetramethoxysilane (TMOS) with different TMOS/(TMOS + TEOS) molar ratio R was carried out to obtain similar to 2.0 x 10(-3) mol SiO2/cm(3) and similar to 86%-volume liquid phase wet gels. Aerogels were obtained by supercritical CO2 extraction in autoclave. The samples were analyzed by small-angle X-ray scattering (SAXS) and nitrogen adsorption. The structure of the wet gels can be described as a mass fractal structure with fractal dimension D similar to 2.2 and characteristic length increasing from similar to 4.6 nm for pure TEOS to similar to 6.4 nm for pure TMOS. A fraction of the porosity is eliminated with the supercritical process. The fundamental role of the TMOS/(TMOS + TEOS) molar ratio on the structure of the aerogels is to increase the porosity and the pore mean size as R changes from pure TEOS to pure TMOS. The supercritical process increases the mass fractal dimension and shortens the fractality domain in the mesopore region. A secondary structure appearing in the micropore region of the aerogels can be described as a mass/surface fractal structure with correlated mass fractal dimension D-m similar to 2.6 and surface fractal dimension D-s similar to 2.3. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: diffraction and scattering measurements; porosity; silica; aerogels; medium-range order; adsorption